2015
DOI: 10.1080/1060586x.2015.1016283
|View full text |Cite
|
Sign up to set email alerts
|

Multi-level voting and party competition in vertically simultaneous elections: the case of Ukraine

Abstract: Vertically simultaneous elections to statewide and regional legislatures provide us with a naturally occurring experiment in which to examine regionalism and multi-level voting. We examine the 2006 vertically and horizontally simultaneous statewide and regional elections in Ukraine to determine how the internal dynamics of regionalism within a state account for the dissimilarity of voting behaviour across electoral levels. Drawing on the party competition literature we demonstrate that variations in both suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…Evidence from voter surveys held in Scotland and Wales clearly reveal a pattern of multilevel or dual voting based on territorial interests and spurred by regionalist parties such as Plaid Cymru and the Scottish National Party (Scully, Jones, and Trystan 2004;Trystan, Scully, and Wyn Jones 2003;Wyn Jones and Scully 2006). Territorial cleavages also drive regional voting in autocratic regimes or new democracies as, for example, is shown in the case of Ukraine (Henderson and Romanova 2016).…”
Section: Addressing Methodological Nationalism In Electoral Researchmentioning
confidence: 98%
“…Evidence from voter surveys held in Scotland and Wales clearly reveal a pattern of multilevel or dual voting based on territorial interests and spurred by regionalist parties such as Plaid Cymru and the Scottish National Party (Scully, Jones, and Trystan 2004;Trystan, Scully, and Wyn Jones 2003;Wyn Jones and Scully 2006). Territorial cleavages also drive regional voting in autocratic regimes or new democracies as, for example, is shown in the case of Ukraine (Henderson and Romanova 2016).…”
Section: Addressing Methodological Nationalism In Electoral Researchmentioning
confidence: 98%
“…The electoral losses of small parties that won the 2006 parliamentary elections -the socialists and the communists -at regional elections were less obvious. Moreover, there were more cases when they scored slightly better at regional elections than at parliamentary elections in the same regions (Henderson & Romanova, 2011).…”
Section: Regional Elections In Ukraine 43mentioning
confidence: 99%
“…Large-N research on turnout at simultaneous multi-level elections has not found much variation across electoral arenas (Schakel and Dandoy, 2010). An in-depth study on simultaneous parliamentary and regional elections in Ukraine in 2006 found that multi-level voting in an institutionally centralised country with severe regional diversity can be dissimilar, even in regions where regional parties do not win seats in regional assemblies (Henderson and Romanova, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Source: Tables 2-7 have been compiled by the author. Table 8 has been compiled from Henderson and Romanova (2011). Notes: Tables 2-8 present the difference between party vote shares at parliamentary and regional elections in the same regions.…”
Section: 10mentioning
confidence: 99%
See 1 more Smart Citation